การศึกษาบทบาทผู้บริหารขององค์การปกครองส่วนท้องถินในจังหวัดสิงห์บุรี - ปลูกรักษ์, ชานิตา (RMUTSB ACADEMIC JOURNAL, 2015)
องค์การปกครองส่วนท้องถิ่นเป็นองค์การที่มีบทบาทและความสำคัญในการบริหารราชการแผ่นดินของไทย เนื่องจากเป็นหน่วยการปกครองที่ใกล้ชิดประชาชนและชุมชนมากที่สุด จังหวัดสิงห์บุรีเป็นจังหวัดขนาดเล็กประกอบด้วย องค์การบริหารส่วนจังหวัด 1 แห่ง เทศบาล 8 แห่ง และองค์การบริหารส่วนตำบล 33 แห่ง มีการแบ่งผู้บริหารออกเป็น 3 ระดับ คือ ระดับสูง ระดับกลาง และระดับต้น โดยผู้บริหารแต่ละระดับจะมีอำนาจหน้าที่ ความรับผิดชอบ และบทบาทแตกต่างและลดหลั่นเป็นไป ตามที่กฎหมายกำหนด ผู้วิจัยจึงสนใจศึกษาบทบาทการบริหารงานของผู้บริหารขององค์การปกครองส่วนท้องถิ่นในจังหวัดสิงห์บุรี โดยมุ่งศึกษาผู้บริหารที่เป็นข้าราชการประจำในแต่ละระดับตำแหน่งหน้าที่ ได้แก่ ระดับสูง (ปลัด และรองปลัด) ระดับกลาง (ผู้อำนวยการกอง หรือหัวหน้ากอง) และระดับต้น (หัวหน้าฝ่าย หรือหัวหน้างาน) และนำมาเปรียบเทียบ และวิเคราะห์เชื่อมโยงความสัมพันธ์ ทำการศึกษาโดยระเบียบวิธีวิจัยเชิงคุณภาพ เก็บรวบรวมโดยการสัมภาษณ์เจาะลึก และการสนทนากลุ่มจากผลการศึกษาสรุปได้ว่า (1) บทบาทด้านการวางแผน พบว่า ผู้บริหารระดับสูงมีบทบาทมากที่สุด (2) บทบาทหน้าที่ด้านการจัดองค์การหรือการจัดระบบงาน พบว่า ผู้บริหารระดับกลางมีบทบาทมากที่สุด (3) บทบาทหน้าที่ด้านการนำองค์การ พบว่า ผู้บริหารระดับสูงมีบทบาทมากที่สุด และ (4) บทบาทหน้าที่ด้านการควบคุมงานและการประเมินผลการปฏิบัติงาน พบว่า ผู้บริหารระดับกลางมีบทบาทมากที่สุด นอกจากนี้ยังพบว่า บทบาทการบริหารของผู้บริหารองค์การปกครองส่วนท้องถิ่นในจังหวัดสิงห์บุรีทุกระดับมีความสอดคล้องสัมพันธ์และมีบทบาทในการบริหารงานร่วมกันในทุกๆ ด้าน The study of the management role of bureaucratic administrators of the local authorities in Singburi province Local authority organization played a vital role in the Thai public administration because the organizations could be considered as the closest organization for the people and communities. Singburi province is a small province. The local authorities here consisted of 1 Provincial Administrative Organization (PAO), 8 Municipalities and 33 Sub-district Administrative Organization (SAO). The management levels had been divided into 3 levels which were the top level, the middle level and the beginning level. The administrator of each level had different authorities, functions, roles and responsibilities according to the central law. The researcher was interested in studying the roles and responsibilities of bureaucratic administrators of the local authorities in Singburi province. The researcher studied and focused on the senior official of each level, for example, top managers (Municipal Clerk/ Deputy Municipal Clerk), middle managers (Director or leader) and beginning managers (the department manager or the functional manager).Then, the results were compared, analyzed the correlation and linkage in order to understand the compliance. This research was the qualitative research. The data were gathered by the “in-depth interview” and the “focus group interview”. This research revealed that (1) the role of planning in top management level had the highest; (2) the role of management in middle level had the highest; (3) the role of the lead organization in the top management level had the highest; and (4) the role of controlling in the middle level had the highest. It was found that the correlation and linkage from all management had roles of bureaucratic administrators of the local authorities in Singburi province.